System architecture for information processing - Ozkarahan, Esen (Information processing & management, 1991)
Text and fact retrieval efficiency can be achieved only within the framework of a computer system architecture embodying parallel search hardware, intelligent I/O architecture, and effective data partitioning and search strategies. Parallelism by itself is not a panacea. This paper presents the framework of the system architecture and the details of our intelligent I/O architecture called IMSA, data partitioning, and the RAP.3 integrated retrieval system. The RAP.3 system is driven by cluster searching for narrowing the search space. All media documents are converted to special relational formats and searched by relational database and text search commands. An integrated multimedia information system supported by object-oriented database methodology within the RAP.3 system architecture is included as a demonstration.